2012
DOI: 10.1515/htmp-2012-0075
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Gas-Liquid Two-Phase Flow in a Horizontally Placed Hydrophobic Rectangular Channel (Part 2, Influence of Abrupt Contraction)

Abstract: This paper computationally visualizes two phase flow patterns through a horizontally placed hydro philic or hydrophobic rectangular channel with an abrupt contraction. The rectangular duct used in this study has a thickness narrower than the Laplace constant so that the surface tension governs the fluid system rather than the inertia force. In particular, the computed bubble behavior at the abrupt contraction seemed to be a similar nature against the preliminary experimental result. Keywords I IntroductionTwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…α ρ α ρ (8) The turbulent viscosity and kinetic energy of the mixture can be found by using Eqs. (9) and (10), respectively. ρ ϵ…”
Section: Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…α ρ α ρ (8) The turbulent viscosity and kinetic energy of the mixture can be found by using Eqs. (9) and (10), respectively. ρ ϵ…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Eskin and Deniz [8] The Eulerian approach was usedwith RMS turbulent model for twophase flow through sudden enlargement. It was observed that the deviation between the numerical values of void fraction and the pressure difference with the experimental values was increased with the increase of the void fraction.Ueda et al [9] used The volume of fluid VOF model, which includes the effect of wall adhesion and surface tension on flow, it was successfully predicted for the bubble flow pattern for low gas discharge and annular flow pattern for high gas discharge.Kumer [10] Performed numerically simulation for water oil two-phase stratified flow in the horizontal and inclined pipes by using volume of fraction (VOF) approach and RNG k-ε turbulence model. The angle of inclination had been ranged from ±50, 00, ±100 from the horizontal.…”
Section: Introductionmentioning
confidence: 99%